9th Biennial Conference of the Australian Pattern Recognition Society on Digital Image Computing Techniques and Applications (D 2007
DOI: 10.1109/dicta.2007.4426799
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Compensation for Fisheye Lenses in UAV Applications

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Fig. 20 shows the performance of the mosaic process while in the turn of [20][21][22][23][24][25][26][27][28][29][30] • . While the images from below the aircraft (using the distorted part of the lens) are reasonable in clarity, there is still some remaining distortion, and also, the registration of these images is worse than the straight and level case, with the latter fact being due to the limitations of the attitude solution in turns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 20 shows the performance of the mosaic process while in the turn of [20][21][22][23][24][25][26][27][28][29][30] • . While the images from below the aircraft (using the distorted part of the lens) are reasonable in clarity, there is still some remaining distortion, and also, the registration of these images is worse than the straight and level case, with the latter fact being due to the limitations of the attitude solution in turns.…”
Section: Discussionmentioning
confidence: 99%
“…Through the observation of numerous images, it could be observed that the distortion of the projected fish-eye image changed relative to the sensor array (a component of the lens moves relative to the sensor). To automatically compensate for the vibration, we used a novel approach based on the application of the Hough transform applied to the partially available fish-eye image circle boundary [24]. Fig.…”
Section: ) Compensation Of a Vibrating Lensmentioning
confidence: 99%
“…Raw image outputs from the handheld and the Zenmuse cameras produced images with dimensions that were too large and would exceed processor memory capacity. To begin, every input image was cropped to dimensions of 2,880 × 2,880 pixels to remove the “fish-eye” effect that often accompanies aerial imagery (Gurtner et al 2007). Next, these images were tiled into smaller dimensions of 1,024 × 1,024 pixels using Python 3.9.7 (Python Software Foundation 2022) and the Pillow module (Clark 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Other studies that investigated the effect of sUAS vibration on image quality were performed by the authors of [14,15]. The latter study not only focused on vibration but also investigated other aspects such as lens calibration, orthorectification and mapping.…”
Section: Methodsmentioning
confidence: 99%
“…The sUAS has variations approximately twice of the variations on the Cessna 172. In [14], where the focus of the investigation was on vibration effects and compensation, the vibration was divided into rotation and translational vibrations. The largest translational movement detected was ±5 pixels measured from randomly selected images.…”
Section: Methodsmentioning
confidence: 99%